KORUPSI DI INDONESIA DALAM PERSPEKTIF HUKUM PIDANA ISLAM - Fazzan Fazzan (Universitas Islam Negeri Ar-Raniry, 2015)
Corruption is a crucial problem in Indonesia that could not be resolved yet. Corruption takes place nearly in all aspect of life and makes Indonesia become a foremost country in corruption. In fact, the majority of Indonesians are Muslim. This study aims to define the perspective and the concept of corruption according to Islamic law in Indonesia. This study used descriptive-analytic method and normative approach. The result of this study shows that corruption in Indonesia is process of feather one’s nest and others by violating the laws and justice principal (al-‘adalah), accountability (al-amanah) and position’s responsibility. If corruption in Indonesia reviewed to jinayat perspective law, thus it will be the same as ghulul (treachery), al-ghasy (fraud), risywah (bribe), al-hirabah (seizure), and al-ghasab (using other’s own non-permit). Corruption is including to criminal act based on Islamic law and nas (script), because of the deed is deviating nas-nas (scripts), such as khiyanah/ghulul, al-ghasy (fraud), risywah (bribe), al-hirabah (seizure), al-ghasab (using other’s own non-permit) and the last but not least, the doer can be punished.